2019
DOI: 10.1101/594838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antagonistic and auxin-dependent phosphoregulation of columella PIN proteins controls lateral root gravitropic setpoint angle in Arabidopsis

Abstract: Lateral roots of many species are maintained at non-vertical angles with respect to gravity.These gravitropic setpoint angles (GSAs) are intriguing because their maintenance requires that roots are able to effect gravitropic response both with and against the gravity vector.Here we have used the Arabidopsis lateral root in order to investigate the molecular basis of the maintenance of non-vertical GSAs. We show that gravitropism in the lateral root is angledependent and that both upward and downward gravirespo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 53 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…1C). Since the effect of auxin and CK in governing GSA is already explored (Rosquete et al 2013(Rosquete et al , 2018Roychoudhry et al 2013Roychoudhry et al , 2019Waidmann et al 2019), we wanted to identify the role of other hormones in modulating this response. The Arabidopsis WT seedlings did not display any changes in branching angle when grown in brassinosteroids (BR), gibberellic acid (GA 3 ), 1-aminocyclopropane-1-carboxylic acid (ACC) or abscisic acid (ABA) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). Since the effect of auxin and CK in governing GSA is already explored (Rosquete et al 2013(Rosquete et al , 2018Roychoudhry et al 2013Roychoudhry et al , 2019Waidmann et al 2019), we wanted to identify the role of other hormones in modulating this response. The Arabidopsis WT seedlings did not display any changes in branching angle when grown in brassinosteroids (BR), gibberellic acid (GA 3 ), 1-aminocyclopropane-1-carboxylic acid (ACC) or abscisic acid (ABA) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, phytohormones have profound effects on determining GSA. For example, as mentioned above, recent findings have identified the fundamental role of auxin in governing the GSA of shoot branches and LRs of Arabidopsis thaliana and other vascular plants, such as rice and beans (Rosquete et al 2013;Rosquete, Waidmann & Kleine-Vehn 2018;Roychoudhry, Del Bianco, Kieffer & Kepinski 2013;Roychoudhry et al 2017Roychoudhry et al , 2019.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, PP2A proteins dephosphorylate PIN1 proteins, leading to their basal location (Costa et al, 2020). Other studies have also shown that PIN3 and PIN7 proteins expressed in the columella region have their subcellular location at the root, and this varies according to the orientation of the gravitational field (Roychoudhry et al, 2019). Furthermore, the dynamic distribution of the PIN proteins on different sides of cells (transcytosis) is responsible for rapid changes in the polarity of the PIN protein, which allows auxin efflux to be quickly redirected in response to environmental signals (Costa et al, 2020;Qi et al, 2020).…”
Section: Auxin Transport and Distributionmentioning
confidence: 99%
“…In nodular roots of Elaeagnus umbellata, the gene EuNOD-ARP1 (Auxin Repressed Protein) was identified, which encodes a cytosolic protein with a higher level of expression in the zone of nodule fixation in roots than in leaves (Kim et al, 2007). Studies have reported the influence of strigolactone signalling on auxin transport, where mutants of Arabidopsis with high expression of the auxin efflux transporters PIN1 and PIN3 showed increased auxin transport capacity, indicating that strigolactones act directly on apical dominance and repress auxin transport, which prevents auxin synthesized in the lateral shoots from being transferred to the main stem (Banasiak et al, 2019;Roychoudhry et al, 2019;Zwiewka et al, 2019). Expression analysis showed that 48 genes are co-regulated by auxin and brassinosteroid (BR), including SAUR (SMALL AUXIN UP-REGULATED RNAs), Aux/IAA, and GH3 (GRETCHEN HAGEN3) (Hirano et al, 2017;Spartz et al, 2017).…”
Section: Gene Expression Regulated By Auxinmentioning
confidence: 99%